Designing a Visit Schedule for Longitudinal Studies in Pediatric Research - Hirschfeld, Steven; Dellarco, Michael; Nowinski, Cindy J.; Slotkin, Jerry (Frontiers in Pediatrics, 2022)
A challenge for longitudinal studies is combining individual assessments into visits that are scientifically logical, not burdensome for participants, well-choreographed, and operationally feasible. The visits then need to be sequenced and spaced to address the scientific goals and generate a data archive that is sufficiently robust and well-documented to support subsequent analyses. This paper summarizes comprehensive multi-disciplinary activities that were coordinated to design the content, format, and structure of the National Children’s Study and concurrently serve as a model and resource for other studies.